Security and privacy issues in sensor networks and IoT - Ahlawat, Priyanka, 1982-; Dave, Mayank, 1967- (Advances in information security, privacy, and ethics (AISPE) book series., 2020)
"This book examines developments, challenges, and research trends in security and privacy issues in sensors networks and the internet of things"--